Impulsivity and Venturesomeness in an Adult ADHD Sample: Relation to Personality, Comorbidity, and Polygenic Risk - Grimm, Oliver; Weber, Heike; Kittel-Schneider, Sarah; Kranz, Thorsten M.; Jacob, Christian P.; Lesch, Klaus-Peter; Reif, Andreas (Frontiers in Psychiatry, 2020)
While impulsivity is a basic feature of ADHD, no study explored the effect of different components of the Impulsiveness and Venturesomeness (IV7) scale on psychiatric comorbidities and an ADHD polygenic risk score (PRS). We used the IV7 self-report scale in an adult ADHD sample of 903 patients 70% suffering from additional comorbid disorders and in a subsample of 435 genotyped patients. Venturesomeness, unlike immediate Impulsivity, is not specific to ADHD. We consequently analysed the influence of Imp and Vent also in the context of a polygenic risk score on psychiatric comorbidities of ADHD. Vent shows a distinctly different distribution of comorbidities, e.g. less anxiety and depression. PRS showed no effect on different ADHD comorbidities, but correlated with childhood hyperactivity. In a complementary analysis using principal component analysis with DSM-IV-ADHD-criteria, NEO-PI-R, Imp, Vent and PRS, we identified three ADHD subtypes. These are an impulsive- neurotic type, an adventurous-hyperactive type with a stronger genetic component, and an anxious- inattentive type. Our study thus suggests the importance of adventurousness and the differential consideration of impulsivity in ADHD. The genetic risk is distributed differently between these subtypes, which underlines the importance of clinically motivated subtyping. Impulsivity subtyping might give insights into the organization of comorbid disorders in ADHD and different genetic background.